Unnoticed Semantic Polonisms in the Chancery language of the Muscovite State - Гарбуль, Людмила Павловна (Slavistica Vilnensis, 2017)
This article examines the history of the following words found in the 17th c. Muscovite State diplomatic correspondence: nasaditi ‘appoint, nominate; invest with authority’, nasaditisja ‘put smb. hostilely, with enmity against smth.; be up in arms (against); threaten, imperil’, nužnyj ‘poor, beggarly, squalid, miserable; meagre, scanty; bad, nasty’, oprava ‘repair(s), repairing; restoration, renewal; improvement’, pobrati ‘take away, bereave of; take possession of, seize’, privernuti ‘return, restore, recover’, strašlivyj ‘terrible, frightful, horrific’, sumnen’e ‘conscience’, teplica (-y) ‘a locality with hot springs; pl. health resort with hot springs’. The author argues that these words, in the meanings provided above, are probably semantic calques from Polish in the Russian written language of the 16th and 17th centuries, which were borrowed likely through mediation of the written language of the Great Duchy of Lithuania, with the exception of nasaditi.
Keywords: semantic loan words/calques; semantic Polonisms; diplomatic correspondence; the written language of the Great Duchy of Lithuania (the Chancery language and the prostaja mova)